Analysis and Optimization of Laying Process Parameters of Carbon Fiber Reinforced Thermoplastic Composites for Additive Manufacturing Using Robot - Liu, Zhiqiang; Li, Yinqi; Hao, Yi; Ma, Zhihao; Gu, Xianan (International journal of precision engineering and manufacturing, 2024)
The research object of this paper is carbon fiber reinforced thermoplastic composite CF/PEEK. Through control planning of robot motion, simulation and experiment on Paving pressure and paving speed are carried out, and on this basis analysis and optimization are carried out. In the analysis of laying pressure, the deformation of rigid press roll and flexible press roll under different pressures is analyzed by finite element simulation. According to the laying experiment, it is certain that the flexible press roll can obtain better laying quality when laying; different pressures are selected to lay the tow. The laying range of these pressures is determined as 50–250 N according to the quality of the tow. In the temperature experiment, the temperature change of the tow in different layers under different laying speeds is analyzed. Through the experiment, it is found that there is a strong correlation between the laying speed and the laying temperature. The experiment also found that under a certain laying speed, selecting the corresponding heating temperature range can obtain higher laying quality and that selecting appropriate paving process parameters, conducting paving tests, and conducting trajectory planning based on the process can effectively reduce paving defects. Finally, in order to solve the problem of path planning for thin-wall structure carbon fiber placement, a natural path algorithm based on Laplace smoothing is proposed. The algorithm obtains the grid surface through the discretization of the thin-walled surface structure, smooths the grid using the Laplace method, and uses the natural path method to obtain the trajectory. At the same time, the algorithm also considers the layout path boundary and layer design, etc. The problem is to complete the trajectory planning through the fiber path assisted generation software and compare the trajectory points with the traditional surface mesh method to verify the rationality of the trajectory algorithm.